La donna mostro. L’"aging" nella commedia all’italiana fra generi e genere (Schermi. Storie e culture del cinema e dei media in Italia, 2022)
Sacred monsters: this is how most of the Italian media and public call actors Gassman, Mastroianni, Tognazzi, Manfredi, Sordi, to mark their legendary status in the Italian history of cinema. Comedy in particular is strongly associated with, and often defined by, the presence of these immensely popular male stars. However, this same period of time, this unique genre, has often relegated female figures to fixed stereotypes (the young maiden, the older woman, the mature one). How can we investigate such a complex phenomenon as the Commedia all’Italiana from a gender point of view? For example, by observing the different representations of time and of the aging process in the bodies of actors, actresses and characters (with particular attention to the works of Antonio Pietrangeli). In this way perhaps we will find another kind of “monstrosity”: female otherness, constantly looking for its (uncomfortable) position within movies that are unapologetic representations of the male gaze.